Thrombosis, major bleeding, and mortality in 1079 patients with myelofibrosis: a matched population-based study - Anneli Enblom Larsson; Henrik Renlund; Björn Andréasson; Henrik Holmberg; Maria Liljeholm; Anders Själander (Blood Advances)
Abstract: Bleeding and thrombotic events are known complications in myeloproliferative neoplasms (MPNs), but few studies have exclusively focused on patients with myelofibrosis (MF). In this nationwide population-based study, we assessed the frequency of major bleeding, thrombotic events, and all-cause mortality in 1079 patients diagnosed with MF and 5395 matched controls using multiple Swedish health care registers. Major bleeding, arterial, and venous events were seen at a rate of 2.55, 2.59, and 1.06 events per 100 years, respectively, in patients with MF. Compared to controls, the rates of bleedings, arterial events, venous events, and mortality were increased, with hazard ratios of 3.78 (95% confidence interval [CI], 2.98-4.79; P < .001), 1.73 (95% CI, 1.40-2.12; P < .001), 2.75 (95% CI, 1.93-3.90; P < .001), and 3.92 (95% CI, 3.50-4.40; P < .001), respectively. Patients treated with JAK inhibitors (JAKis) had higher rates of major bleeding (5.33), arterial events (4.67), and venous events (1.56) than patients with no ongoing symptom–directed therapy (rates, 2.32, 2.15, and 0.79) or hydroxyurea (rates, 2.05, 2.35, and 1.27, respectively). The use of JAKis or low-molecular-weight heparin, previous arterial or venous events, and older age were identified as independent risk factors for new arterial or venous events. A previous venous event, higher leukocyte count at diagnosis, and ongoing JAKi treatment were associated with an increased risk of major bleeding. This study shows that patients with MF have higher rates of thromboembolic events and major bleeding than described in other MPNs, and thromboembolic complications and major bleeding diverge in the different treatment groups.